Novel Path Inference in Large Scale Wireless Networks Using Sensors - Chowdary, Katta Sindhu; Nyaramneni, Sarika (International Journal of Computer Sciences and Engineering, 2019)
Recent wireless sensor networks (WSNs) are getting progressively advanced with developing network scale and therefore dynamic nature of wireless communications. Several diagnostic approaches depend upon per-packet routing ways for correct and fine-grained analysis of the advanced network behaviors. Here we analyzed various path inference approaches to reconstruct routing paths. Based on the earlier contribution and recent studies, iPath provides an efficient and optimal routing path and iPath achieves much higher reconstruction ratios under different network settings compared to other state of the art approaches. The main theme of ipath is to construct a long path from the known short paths. This Process starts with primary paths and then conducts path inference repeatedly.